2008
DOI: 10.1177/0363546508325153
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis Examining Clinical Test Utility for Assessing Superior Labral Anterior Posterior Lesions

Abstract: The anterior slide test is a poor test for detecting the presence of a labral lesion in the shoulder. Active compression, crank, and Speed tests are more optimal choices. Clinicians should choose the active compression test first, crank second, and Speed test third when a labral lesion is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…O'Brien's test was classically described for the diagnosis of SLAP tears [18], but recent studies suggest it is useful for identifying labral pathology in general in conjunction with other provocative tests [11,16]. O'Brien's test is believed to produce pain by applying tension across the biceps labral complex and by tensioning the capsule again an unstable labrum [18].…”
Section: Discussionmentioning
confidence: 99%
“…O'Brien's test was classically described for the diagnosis of SLAP tears [18], but recent studies suggest it is useful for identifying labral pathology in general in conjunction with other provocative tests [11,16]. O'Brien's test is believed to produce pain by applying tension across the biceps labral complex and by tensioning the capsule again an unstable labrum [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, authors of 3 previous studies and a meta-analysis indicated poor diagnostic utility of the anterior slide for either confirming or excluding a SLAP lesion. 6,7,15,20 Our study indicated that the anterior slide test probably has limited diagnostic utility as a single test. In light of our findings and those of previous investigators, 6,7,15,20 the anterior slide test should be used with caution as a single test to diagnose type II to IV SLAP lesions.…”
Section: Disclaimermentioning
confidence: 81%
“…7,9,10,12 In systematic reviews of studies in which tests for SLAP lesions were investigated, authors have indicated that no single test or combination of tests consistently has demonstrated adequate diagnostic utility for identifying SLAP lesions. 13,14 However, in their meta-analysis of SLAP lesion tests using summary receiver operating characteristic (ROC) curves, Meserve et al 15 reported that the active compression and crank tests had better diagnostic utility than the anterior slide test for determining SLAP lesions; the anterior slide test was not recommended for use.…”
mentioning
confidence: 99%
“…16,25,[42][43][44][45] However, 2 tests for the examination of SLAP tears deserve further analysis, provided later. The influence of combining tests to increase clinical utility is also summarized later.…”
Section: Superior Labrum Anterior and Posterior Lesionsmentioning
confidence: 99%